Peripheral pockets of paradise perceptions of health and geography in early twentieth-century Manila and its environs - Pante, Michael D. (Philippine studies : historical and ethnographic viewpoints, 2011)
"By constantly blaming Manila's low-lying topography and tropical climate, the "health-conscious" American colonial state revealed the significance that geography played in its perception of health. At the same time, this peculiar perception also revealed a flipside. As this article argues, the colonial state and the elite envisioned "a geography of health" typified by the breezy, elevated, sparsely-populated suburbs east of Manila that seemed "familiar" to the colonizers. As the districts of Santa Mesa and San Juan del Monte became representations of these ideals, the two areas underwent a process of suburbanization in the early twentieth century with the aid of transport "modernization."